Hypoxia induces a hedgehog response mediated by HIF‐1α - Bijlsma, Maarten F. (J Cell Mol Med, 2008)
Recently, it has become clear that the developmental hedgehog pathway is activated in ischaemic adult tissue where it aids in salvaging damaged tissue. The exact driving force for the initial hedgehog response is unclear and as most physiological and cellular processes are disturbed in ischaemic tissue, hedgehog‐activating signals are hard to dissect. Here, we demonstrate that hypoxia per se is able to induce a rapid systemic hedgehog response in adult mice, as evident from expression of the pathway ligand, Sonic hedgehog, as well as the pathway activity marker Patched1 in various organs. Using in vitro models of hypoxia, we showed that the hedgehog response was transient and preceded by the accumulation of HIF‐1α, which we hypothesized to communicate between hypoxia and hedgehog expression. Indeed, pharmacological inhibition, knockdown or genetic ablation of HIF‐1α abolished hedgehog pathway activation. In conclusion, we have established that hypoxia is translated into a hedgehog response through HIF‐1α and this mechanism is likely to be responsible for the hedgehog response observed in various ischaemia models.